False-positive fourth-generation HIV test associated with autoimmune hemolytic anemia. Case report - Santiago Sánchez-Pardo; Jaime Andrés Osorio-Ramírez; Isabela Choi-Park; Daniel Felipe Rojas-Holguín; Adrián Bolívar-Mejía (Case Reports)
Introduction: The fourth-generation ELISA human immunodeficiency virus (HIV) screening test has a high sensitivity and specificity >99% to detect both antigens and antibodies. Estimates are that only 0.5% yield false positive results.